Exigência de valina digestível para frangos de corte fêmeas - Pereira, Thuani Venâncio da Silva (2018)
The present study aimed to determine the levels of digestible valine to female broilers. Three experiments were carried out with female broiler of Coob in pre-initial phase (1 a 7 days), initial (8-21 days) and growth (22 a 42 days). For tests 1 a 7 days and 8 a 21 days, 735 animals it werw distributed in a completely randomized in seven treatments (valine levels), with seven replicates and each experimental unit compsed of 15 birds. For test of 22 to 42 days 637 chickens were used, equally distributed as in previous trials in 7 treatments with 7 replicates of 13 birds each. Basal diet were formulated by the dilution technique, containing levels of energy, minerals and vitamins as recommended by Rostagno et al., (2011) for each phase. The treatments consisted of the initial (8.82, 9.32, 9.82, 10.32, 10.82, 11.32, 11.82 g/kg ration), initial phase (7.74, 8.24, 8.44, 9.24, 9.74, 10.24, 10.74 g/kg ration) and for growth phase (6.33, 6.83, 7.33, 7.83, 8.33, 8.83, 9.33 g/kg ration). The following performance characteristics, serum levels of uric acid, visceral organ weight and length, carcass yield and cuts commercial. The recommended levels of digestible valine obtained in this study for each phase were based on feed conversion or weight gain responses. For three phases there was quadratic effect for weight gain. The had linear decrease in feed intake, while feed conversion showed a quadratic effect for pre-initial phase. In the growth phase there was a quadratic effect for feed intake. For the yield variables carcass, sobrecoxa and liver, linear effect. In relation to the proventriculus, gizzard, pancreas, duodenum, ileum and large intestine there was quadratic effect for yield and length.In general, with the increase in L-Valine levels, a reduction in feed intake, weight gain, carcass yield and increased uric acid excretion was observed, demonstrating that levels above the requirement of the birds may be detrimental to performance.The recommendations obtained by the dose responsare are 10,03; 9,23 and 7,77g/kg of digestible valine for broilers from 1- 7 days, 8-21 and 22 a 42 days of age, respectively.